2023
DOI: 10.1002/advs.202305505
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Walden Inversion for the Activity Volcano Plot of Oxygen Evolution

Kai S. Exner

Abstract: Since the birth of the computational hydrogen electrode approach, it is considered that activity trends of electrocatalysts in a homologous series can be quantified by the construction of volcano plots. This method aims to steer materials discovery by the identification of catalysts with an improved reaction kinetics, though evaluated by means of thermodynamic descriptors. The conventional approach for the volcano plot of the oxygen evolution reaction (OER) relies on the assumption of the mononuclear mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Figure 4 d). 4 This view is further substantiated by a recent computational study on the oxygen reduction of a Fe–N–C catalyst where a Walden step was identified as the RDS under reaction conditions. 45 In summary, the fourth generation of volcano plots has improved their mechanistic description by moving beyond a single pathway and including the possibility of concurrent adsorption–desorption processes in the realm of Walden-type steps in the analysis.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Figure 4 d). 4 This view is further substantiated by a recent computational study on the oxygen reduction of a Fe–N–C catalyst where a Walden step was identified as the RDS under reaction conditions. 45 In summary, the fourth generation of volcano plots has improved their mechanistic description by moving beyond a single pathway and including the possibility of concurrent adsorption–desorption processes in the realm of Walden-type steps in the analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Figure c), and volcano plots by the descriptor G max ( U ) underpin their relevance to the description of the oxygen electrocatalysis: particularly highly active OER catalysts may follow a Walden pathway rather than the conventional description of sequential desorption and adsorption steps (cf. Figure d) . This view is further substantiated by a recent computational study on the oxygen reduction of a Fe–N–C catalyst where a Walden step was identified as the RDS under reaction conditions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations